Influence of Epinastine Hydrochloride, an H1-Receptor Antagonist, on the Function of Mite Allergen-Pulsed Murine Bone Marrow-Derived Dendritic Cells In Vitro and In Vivo - Ken-Zaburo Oshima; Kazuhito Asano; Ken-Ichi Kanai; Miyuki Suzuki; Harumi Suzaki (Mediators of Inflammation)
There is established concept that dendritic cells (DCs) play essential roles in the development of allergic immune responses. However, the influence of H1 receptor antagonists on DC functions is not well defined. The aim of the present study was to examine the effect of epinastine hydrochloride (EP), the most notable histamine H1 receptor antagonists in Japan, on Dermatophagoides farinae (Der f)-pulsed mouse bone marrow-derived DCs in vitro and in vivo. EP at more than 25 ng/mL could significantly inhibit the production of IL-6, TNF-𝛼 and IL-10 from Der f-pulsed DCs, which was increased by Der f challenge in vitro. On the other hand, EP increased the ability of Der f-pulsed DCs to produce IL-12. Intranasal instillation of Der f-pulsed DCs resulted in nasal eosinophilia associated with a significant increase in IL-5 levels in nasal lavage fluids. Der f-pulsed and EP-treated DCs significantly inhibited nasal eosinophila and reduced IL-5. These results indicate that EP inhibits the development of Th2 immune responses through the modulation of DC functions and results in favorable modification of clinical status of allergic diseases.